2012
DOI: 10.4137/cmped.s8407
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deficiency and Sleep Health Problems in Chinese Adolescents

Abstract: A survey of sleep schedules, sleep health, and the impact on school performance was conducted in 585 adolescents in a high school in China. A high level of early and circadian-disadvantaged sleep/wake schedules during weekdays was observed. Significantly shorter sleep duration on weekdays was reported (P < 0.0001). Older teenagers slept significantly less than the younger teenagers (P < 0.0001). Complaints of inadequate sleep and sleepiness during weekdays were prevalent. Night awakenings were reported in 32.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…In the Roberts's study, it was found that 0.06% of adolescents had a sleep disorder that was lower than that of the present study [32]. In the study by Kaneita et al, 11.3% of adolescents had sleep disorders, 5.5% had impaired sleep [11], and 24.7% had a sleep deprivation feeling during the day. The origin of the disorder at the onset and continuation of sleep and daytime sleepiness in adolescents can be in the psychological and family conditions of the adolescent or early wake-up in the morning to go to school or watching television a lot.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In the Roberts's study, it was found that 0.06% of adolescents had a sleep disorder that was lower than that of the present study [32]. In the study by Kaneita et al, 11.3% of adolescents had sleep disorders, 5.5% had impaired sleep [11], and 24.7% had a sleep deprivation feeling during the day. The origin of the disorder at the onset and continuation of sleep and daytime sleepiness in adolescents can be in the psychological and family conditions of the adolescent or early wake-up in the morning to go to school or watching television a lot.…”
Section: Discussioncontrasting
confidence: 66%
“…Adolescent's sleep has a great role in the healthy brain development. Adolescents need more sleep compared to pre-puberty time, but there is much turmoil in their sleep and waking cycles [11]. The reason for sleep disorders in adolescents is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, sleep deprivation is a growing public health concern among the scientific community owing to the long-terms consequences on health and quality of life at individual level, and economic costs in terms of productivity loss at national level. Although most of the findings originate from researches in high-income settings, the epidemic is not unique to the wealthy countries as poverty of sleep is being recognised to be a widespread issue in LMICs as well ( Shah, Bang & Bhagat, 2010 ; Kang et al, 2012 ; Stranges et al, 2012 ). In Africa, on the other hand, the issue has remained underemphasised to date and is potentially contributing to the worsening health outcomes and unmet health need of the population.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, short sleep duration on workdays and extended sleep duration on non-workdays have been observed in many nations over the past decade. 17 – 20 Mounting evidence demonstrates that the societal reductions in sleep may contribute to unhealthy consequences, especially metabolic abnormalities (eg, obesity and type-2 diabetes mellitus). 28 Therefore, whether the risk of unhealthy consequences can be ameliorated by catching up on sleep on weekends and holidays is hotly debated.…”
Section: Discussionmentioning
confidence: 99%